IMPLEMENTASI STRATEGI EXPERIENTIAL LEARNING DALAM PEMBELAJARAN PAI: STUDI PEMBENTUKAN KARAKTER RELIGIUS DAN TOLERANSI PESERTA DIDIK - Oktaviana, Shella; Syafei, Imam; Sri Anggoro, Bambang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the gap between cognitive-oriented Islamic Religious Education (IRE) learning and the internalization of religious character and tolerance attitudes among students. In many classrooms, IRE learning still emphasizes conceptual understanding rather than lived experience, resulting in limited religious practice and social tolerance in daily interactions. This research aims to describe the implementation of the Experiential Learning strategy in IRE learning and analyze its role in strengthening students’ religious character and fostering tolerance attitudes. The study employed a qualitative descriptive approach conducted at a public junior high school in Bandar Lampung. Research participants consisted of IRE teachers and eighth-grade students. Data were collected through classroom observations, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. Data validity was ensured through source and technique triangulation. The findings reveal that Experiential Learning was implemented through stages of concrete experience, reflective observation, abstract conceptualization, and active experimentation. This strategy effectively enhanced students’ religious character, including worship awareness, honesty, responsibility, and social care. Furthermore, it contributed to the development of tolerance attitudes, particularly internal religious tolerance, as reflected in respectful interactions, appreciation of differing opinions, and improved emotional control. The study concludes that Experiential Learning is an effective instructional strategy for Islamic Religious Education oriented toward character building and social attitude development.